2017
DOI: 10.1177/1474515117693891
|View full text |Cite
|
Sign up to set email alerts
|

Impact of comorbidities by age on symptom presentation for suspected acute coronary syndromes in the emergency department

Abstract: Background It is estimated half of acute coronary syndrome (ACS) patients have one or more associated comorbid conditions. Aims Aims were to: 1) examine the prevalence of comorbid conditions in patients presenting to the emergency department with symptoms suggestive of ACS; 2) determine if comorbid conditions influence ACS symptoms; and 3) determine if comorbid conditions predict the likelihood of receiving an ACS diagnosis. Methods A total of 1064 patients admitted to five emergency departments were enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…This is frequently due to clinical guidelines that are based on scientific studies that focus on the primary/index disease and exclude or underrepresent multimorbid patients. 2,12,26,31,34,[36][37][38] Future studies should employ a pragmatic design and focus on health care use following discharge for ACS for patients with multimorbidity.…”
Section: Multimorbidity and Post-discharge Outcomes At 1 Yearmentioning
confidence: 99%
“…This is frequently due to clinical guidelines that are based on scientific studies that focus on the primary/index disease and exclude or underrepresent multimorbid patients. 2,12,26,31,34,[36][37][38] Future studies should employ a pragmatic design and focus on health care use following discharge for ACS for patients with multimorbidity.…”
Section: Multimorbidity and Post-discharge Outcomes At 1 Yearmentioning
confidence: 99%
“…(10) In another study was investigated a similar population, and a similar CCI value was found. (27) In any case, CCI is known as an adequate prognostic indicator to assess the risk of in-hospital mortality in patients with ACS after one year of the event. (25) Together, these data show the clinical severity profile of participants, whether based on the occurrence of complications after AMI or by the impact of comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of T2DM in patients with ACS ranges from one in four4 to more than 50% 5. Globally, patients with ACS and diabetes have more severe types of coronary lesions compared with those without diabetes 6.…”
Section: Introductionmentioning
confidence: 99%